The Chicago Piles unearthed - Andrea Zoia; Albin Gagnepain; Davide Mancusi (Scientific Reports)
Abstract The divergence of the Chicago Pile 1 (CP-1) on December 2nd, 1942 marks the birth of the nuclear age. CP-1 was the first nuclear reactor, conceived as a proof-of-principle physics experiment to demonstrate the feasibility of a self-sustained neutron chain reaction. After only three months of operation, CP-1 was dismantled due to safety reasons and rebuilt at the Argonne Site, under the name of Chicago Pile 2 (CP-2). CP-2 had a longer life, contributing vastly to research on material science and nuclear reactor theory, and was finally decommissioned in 1954. These astonishing scientific artifacts remain poorly characterized, in spite of their pivotal historical role. Here, we fill this gap by building fully detailed three-dimensional digital twins of CP-1 and CP-2 using TRIPOLI-4, the Monte Carlo particle transport code developed at CEA, based on the aggregation of information retrieved from published and unpublished documents of the Manhattan Project. Simulation results faithfully reproduce the available experimental measurements and shed light on the early development of fuel and moderator materials.